Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin